Wpływ inwestycji private equity na działalność badawczo-rozwojową w Europie - Świderska, Joanna (The Influence of Private Equity Investments on Research and Development Activity in Europe, 2007)
Private equity investments (especially venture capital) have recently played an important role, contributing to the expansion of research and development activity, and thus improving innovation ability of European economies. Statistics and the results of researches, commissioned by EVCA among others, show that in companies using venture capital financing every one of three employees has been employed in R&D department, which is over 20 times higher than employment in R&D department in European units altogether. Also average-yearly expenditures on R&D, which are one of the basic measures of economy innovation ability, in companies, financed by venture capital, have been over 6 times higher. The direct result of R&D activity is the number of patent applications. Calculated on 1 million residents, it has been over 600 times higher in the analyzed companies. Taking into account the fact that the effects described above have been mainly a consequence of financing by private equity funds, we can state that these funds have become a pillar of European economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 579-587